Federalism for Bioethics? - Francis, Leslie (Cambridge quarterly of healthcare ethics, 2024)
In the wake of the Dobbs decision withdrawing federal constitutional protection for reproductive rights, the United States is in the throes of federalist conflicts. Some states are enacting draconian prohibitions of abortion or gender-affirming care, whereas other states are attempting to shield providers and their patients seeking care. This article explores standard arguments supporting federalism, including that it allows for cultural differences to remain along with a structure that provides for the advantages of common security and commerce, that it provides a laboratory for confined experiments, that it is government closer to the people and thus more informed about local needs and preferences, and that it creates layers of government that can constrain one another and thus doubly protect rights. We contend that these arguments do not justify significant differences among states with respect to the recognition of important aspects of well-being; significant injustices among subnational units cannot be justified by federalism. However, as nonideal theorists, we also observe that federalism presents the possibility of some states protecting rights that others do not. Assuming that movement among subnational units is protected, those who are fortunate enough to be able to travel will be able to access rights they cannot access at home. Nonetheless, movement may not be readily available to minors, people without documentation, people with disabilities, people who lack economic resources, or people who have responsibilities that preclude travel. Only rights protection at the federal level will suffice in such cases.